Analysis Of Work Discipline In Improving Employee Performance At The General Administration Bureau, Finance And Resources Of Makassar Muhammadiyah University - Reski Dwi Damayanti; Syarifuddin Sulaeman; Nurinaya, Nurinaya (International Journal of Economic Research and Financial Accounting, 2024)
This research is a type of qualitative research with the aim of finding out how work discipline improves employee performance at the General Administration, Finance and Resources Bureau of Muhammadiyah University of Makassar. The type of data used is descriptive qualitative with data collection through observation and interviews. Research results that can be written show that a high level of discipline influences better performance, higher productivity and more consistent target achievement. Factors such as punctual attendance and completing tasks according to schedule are important indicators of the level of work discipline. On the other hand, lack of discipline can result in decreased performance and instability in achieving targets.